Penguatan literasi kesehatan lingkungan melalui sosialisasi resistensi Bakteri Endogen pada kaki Kecoak di Kelurahan Tondo - Kundera, I Nengah; Budiarsa, I Made; Mawaddah, Hayyatun; Rauf, Abd (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2024)
The community in RT.05/RW.13, Tondo Village, Mantikulore District, Palu City, shows a low level of awareness in maintaining environmental cleanliness, particularly in managing household waste. This condition contributes to the spread of pathogenic bacteria through cockroach vectors (Periplaneta americana), which can cause various diseases. This community service program aimed to enhance public health literacy regarding environmental cleanliness, the resistance of endogenous bacteria carried by cockroaches, and to establish the sustainability of environmental health literacy. The program applied the Participatory Action Research (PAR) method, consisting of four stages: to know, to plan, to act, and to change. The program involved 24 residents of RT.05/RW.13 and was conducted on July 26-27 and August 3-5, 2024. Results indicated an improvement in public understanding, with questionnaire results showing an 84% score categorized as good. Additionally, an educational poster about the dangers of cockroaches as disease vectors and their bacterial resistance was developed and installed in the community area. This increase in health literacy is expected to motivate behavioral changes among residents in maintaining environmental cleanliness, ultimately supporting the creation of a healthier environment